Equalization Annual Notification Report Value Added Tax Against the Income Statement of PT. X Through the Accounting Application - D Heriansyah; J Abdillah; Sabar; E Suprihatin (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This research is intended to find out how the implementation of the equalization of the Annual Income Tax Return on the Income Statement at PT. X. This equalization is necessary to test the correctness of the value of the Tax Base on the Company’s Profit and Loss Statement. The method used in this research is the method of direct observation and interviews for collection as well as descriptive analysis methods and comparative analysis with a quantitative approach to the data analysis process. Based on the results of the study it can be concluded that PT. X recognizes that 2020 revenue will be recognized in 2021, so if there is no equalization there will be a difference in the amount of VAT payable, which will also have an impact on the value error in reporting the monthly tax return of PT. X.